Synthesis, Characterization and Crystal Structures of Mixed-Ligand Complexes of [Cu(bipy)2N3(ClO4)] and [Cu(5,5’-DiMebipy)2(N3)](ClO4) - Oluwafunmilayo Florence Adekunle; Ray John Butcher; Oladapo Bakare; Joseph Anthony Orighomisan Woods; Olusegun Ayobami Odunola (Universitas Gadjah Mada, 2016)
Two mixed –ligand complexes [Cu(bipy)2N3(ClO4)] and [Cu(5,5’-DiMebipy)2(N3)](ClO4) have been prepared and characterized. The compounds were characterized by elemental analyses, IR and UV-Visible spectroscopy, room temperature magnetic susceptibility measurements, and conductivity measurement, while the solid-state structures have been established by single-crystal X-ray diffraction analyses. [Cu(bipy)2N3(ClO4)]crystallizes in the monoclinic space group P21/c with cell constants a = 16.9027(3) Å, b = 7.59087(9) Å, c = 17.2614(3) Å, β = 111.2808(19)° and Z = 4. [Cu(5,5’-DiMebipy)2(N3)](ClO4) also crystallizes in the monoclinic space group P21/c with the cell constants a = 16.0312(11) Å, b = 7.9889(5) Å, c = 20.7167(18) Å, β = 110.285(8)° and Z = 4. The UV-Vis spectra and X-ray determination indicate that [Cu(bipy)2N3(OClO3)] is distorted octahedral ligand field and non-electrolyte in nature while [Cu(5,5’-DiMebipy)2(N3)](ClO4) is a square pyramidal five coordinate complex and a 1:1 electrolyte. The magnetic moments of the two complexes in the range 1.78–1.83 B.M. reveal a single unpaired electron with a slight orbital contribution.